Surgical smoke: modern mobile smoke evacuation systems improve occupational safety in the operating theatre. (8th February 2022) - Gioutsos, Konstantinos; Nguyen, Thanh-Long; Biber, Ulrich; Enderle, Markus D; Koss, Abigail; Kocher, Gregor J
Abstract: OBJECTIVES: Evaluation of smoke capture efficiency of different mobile smoke evacuation devices with respect to volatile organic compounds and their noise emission. METHODS: Electrosurgical incisions were performed on fresh porcine liver in an operating room with vertical laminar flow. The generated surgical smoke was analysed with proton-transfer-reaction mass spectrometry with and without the use of a mobile smoke evacuation system consisting of a smoke evacuator machine, a suction hose and a handpiece. The inlet of the mass spectrometer was positioned 40 cm above the specimen. Various devices were compared: a hard plastic funnel, a flexible foam funnel, an on-tip integrated aspirator of an electrosurgical knife and a standard secretion suction (Yankauer). Also, sound levels were measured at a distance of 40 cm from the handpieces' inlet. RESULTS: The smoke capture efficiency of the secretion suction was only 53%, while foam funnel, plastic funnel and integrated aspirator were all significantly more effective with a clearance of 95%, 91% and 91%, respectively. The mean sound levels were 68 and 59 A-weighted decibels with the plastic and foam funnel, respectively, 66 A-weighted decibels with the integrated aspirator and 63 A-weighted decibels with the secretion suction. CONCLUSIONS: Carcinogenic, mutagenic and reprotoxic volatile organic compounds in surgical smoke can be efficiently reduced by mobile smoke evacuation system, providing improved protection for medical personnel. Devices specifically designed for smoke evacuation are more efficient than standard suction tools. Noise exposure for the surgeon was lowest with the flexible foam funnel and higher with the other handpieces tested. Abstract : Surgical smoke contains inorganic, small organic and fragments of larger biological compounds.